The Importance of Academic Information Systems in Higher Education - Arifa Wildana Al Kautsar; Nabila Cahaya Maulida; Joy Nashar Utama Jaya (Green Publisher Indonesia, 2026)
The development of information technology has encouraged universities to improve the quality of academic services through the implementation of digital systems. One form of implementation is the use of the Sistem Informasi Akademik (SIAKAD) or Academic Information System, which supports various administrative processes, including Study Plan Card (Kartu Rencana Studi [KRS]) submission, grade management, lecture scheduling, and the delivery of academic information to students. The presence of this system makes administrative processes more practical, efficient, and accessible to the entire academic community. This research aimed to examine the importance of implementing Academic Information Systems in improving the effectiveness of academic services in higher education. The study employed a literature review method by examining various scientific journals and references related to the implementation of SIAKAD in Indonesia. The collected data were analyzed descriptively to identify the benefits, challenges, and development opportunities of academic information systems. The results showed that SIAKAD implementation provides several benefits, including improved administrative efficiency, easier access to academic information, and enhanced service quality for students and lecturers. However, several challenges remain, including technological infrastructure readiness, user competency in operating the system, and the need for continuous system development to adapt to technological advancements. Therefore, effective management of SIAKAD is an important factor in supporting the improvement of higher education service quality.